Depression among Tuberculosis Patients in Sarawak - Mohd Nor Faizal, Zulkifli; Noorzilawati, Sahak; Rosalia, Saimon (Malaysian Public Health Physicians’ Association, 2025)
Tuberculosis (TB) remains a major public health issue in Malaysia, particularly in Sarawak, which consistently reports high case burdens. Depression is a common comorbidity among TB patients, adversely affecting treatment adherence and outcomes. This study aimed to determine the prevalence and associated factors of depression among TB patients in Sarawak. The prevalence was 9.9%. Bivariate analysis showed associations with social support, patient satisfaction, and treatment side effects, but only stigma and marital status remained significant after adjustment. These findings underscore the need for integrated mental health strategies that address stigma, enhance social support, and improve patient experiences within TB care services.